BLOOD METABOLITES OF BUFFALOES WITH DIFFERENTIAL FERTILITY UNDER UNIFORM FEEDING - DADARWAL, D; GHUMAN, S P S; SINGH, JAGIR; HONPARKHE, M; DHALIWAL, G S; MEHRA, M L (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on 18 anestrus (nulliparous, n=12; pluriparous, n=6) and 12 cycling (nulliparous, n=?; pluriparous, n=5) buffaloes that were blood sampled three times at weekly interval. Plasma samples were analyzed for glucose, total proteins, albumin, urea, creatinine, lipid profile, AST, ALT, LDH, Ca and P. This study reveals that none of the blood metabolites were different between anestrus or cycling nulliparous buffaloes. However, cycling pluriparous buffaloes had higher (p<0.05) plasma glucose, total proteins, albumin, creatinine, LDL and lower (p<0.05) LDH compared to anestrus.